Interactive 3D registration of ultrasound and magnetic resonance images based on a magnetic position sensor. - Pagoulatos, N.
The use of stereotactic systems has been one of the main approaches for image-based guidance of the surgical tool within the brain. The main limitation of stereotactic systems is that they are based on preoperative images that might become outdated and invalid during the course of surgery. Ultrasound (US) is considered the most practical and cost-effective intraoperative imaging modality, but US images inherently have a low signal-to-noise ratio. Integrating intraoperative US with stereotactic systems has recently been attempted. In this paper, we present a new system for interactively registering two-dimensional US and three-dimensional magnetic resonance (MR) images. This registration is based on tracking the US probe with a DC magnetic position sensor. We have performed an extensive analysis of the errors of our system by using a custom-built phantom. The registration error between the MR and the position sensor space was found to have a mean value of 1.78 mm and a standard deviation of 0.18 mm. The registration error between US and MR space was dependent on the distance of the target point from the US probe face. For a 3.5-MHz phased one-dimensional array transducer and a depth of 6 cm, the mean value of the registration error was 2.00 mm and the standard deviation was 0.75 mm. The registered MR images were reconstructed using either zeroth-order or first-order interpolation.
Keywords: 1D array transducer; DC magnetic position sensor; Brain; Custom-built phantom; Errors; First-order interpolation; Image-based surgical tool guidance; Interactive 3D registration; Intraoperative imaging modality; Magnetic position sensor; Magnetic resonance images; Position sensor space; Stereotactic systems; Ultrasound images; Ultrasound probe tracking; Zeroth-order interpolation